The Soundscape of Klaipėda (I): (Un)Heard City - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2017)
This article deals with urban soundscapes. A soundscape is a sonic environment and a multitude of sound sources that reach the human ear. By comparing the different ways in which the soundscape of Klaipėda is constructed, we seek to analyse the aural background of Klaipėda. This research is based on the methodological distinction between hearing and listening. The first is a passive reception of sound, while the latter is interpreted as an activity consisting of both the searching for sounds as well as their interpretation and analysis. The current article concentrates on the hearing mode, which is to be found on the websites that officially represent the city of Klaipėda (Klaipėda Municipality and Klaipėda Tourist and Culture Information Centre websites), the noise regulation rules and the noise maps of Klaipėda, newsletters of the newly built real estate in Klaipėda and its suburbs. The second article will analyse the notion of urban soundscape via the listening mode, concentrating on the practices of sound theorists and sound artists.
Keywords: Klaipeda; urban studies; soundscape; urban sounds; construction of urban soundscape; noise